The Influence of Theory of Planned Behavior, Brand Consciousness, and Perceived Risk on Purchase Intention - Nikolas Endrico Wibowo; Theresia Diah Widiastuti; Helena Yovita Junijanto (Master of Management, School of Business and Management, Petra Christian University, 2024)
This study aims to determine the effect of Attitude, Perceived Behavioral Control, Subjective Norm (Theory of Planned Behavior), brand consciousness, and perceived risk on purchase intention. The sample used in this study consisted of 231 respondents selected through purposive sampling. Respondents who participated were those who belonged to Generation Z (1997-2012) and Generation Y (1981-1996), knew the Nike shoe brand, and had never bought a knock-off product (KW) of Nike shoes. Partial Least Square (SmartPLS) software version 4 was used for Partial Least Square (MGA-PLS) testing in addition to Structural Equation Modeling (SEM). The study's findings indicate that attitude and perceived behavior control positively affect purchase intention, while subjective norm does not. Brand consciousness and perceived risk do not positively affect purchase intention, while perceived risk positively affects Attitude. This study is certainly expected to provide theoretical contributions to the Theory of Planned Behavior, Brand Consciousness, and Perceived Risk, whose relationship can affect a person's purchase intention on counterfeit shoes, and practical contributions can be useful for counterfeit shoe business actors in developing their businesses.